Reflections on Conversations and Memory. (5th August 2019) - Cyr, Travis G.; Hirst, William
Abstract: The study of memory and remembering has traditionally either stripped meaning away from acts of remembering to reveal the "raw material of memory" or explored how meaning guides the reconstruction of the past. In reflecting on the contributions to this topic, there appears to be an emerging "third‐way, " which holds that there is an inextricable relation between conversations and remembering. The articles in this volume exemplify how conversing is often an act of remembering and represent approaches to memory that might not otherwise be taken if one were to study memory as a within‐individual phenomenon. The implications of this approach are far‐ranging and present the opportunity to pose new questions about the nature of remembering as it unfolds in conversation. The contributing articles have expanded the scope of what memory researchers can study by adopting a relatively straightforward assumption about the sociality of remembering and the role of the conversation in the social process. Abstract : Hirst distills the relevant and common themes that have been discussed throughout this topic. He successfully integrates the various interdisciplinary works on the dynamics and outcomes associated with conversational remembering and how it is currently changing due to social media. Notably, he ends with thoughts about the future of conversational remembering research and areas of future research.